Exploring the meaning of night shift placement in nursing education: A European multicentre qualitative study. (December 2020) - Dobrowolska, Beata; Visintini, Chiara; Pokorná, Andrea; Nascimento, Carla; Ferrão, Sónia; Ziakova, Katarina; Solgajova, Andrea; Rybarova, Lubica; Machul, Michał; Lunazzi Gorizza, Giulia; Palese, Alvisa
Abstract: Background: An appropriate clinical learning environment has been identified as pivotal in nursing undergraduate education and should be planned responsibly. Specifically, night shifts placements have been documented as an important opportunity for developing a full understanding of the nursing profession and the whole process of nursing care. However, night shifts during placement have been reported to be stressful and anxiety-provoking, so their usefulness for nursing students is still debated. Objectives: To elicit nursing students' perceptions of night shift placement through metaphors, with the aim of discussing the pedagogical and ethical implications. Design: A descriptive qualitative study was performed based on metaphors collected in an international cross-sectional study in 2016. Settings: A network comprising five Bachelor of Nursing Science degrees located in the Czech Republic, Italy, Poland, Portugal, and Slovakia was established. Methods: A total of 907 out of 1347 eligible nursing students from the five European countries described their learning experience on night shifts using a metaphor. Results: Overall, 288/907 (31.7%) metaphors emerged as being negative-oriented and 137/907 (15.1%) as positive, while the remaining students (482; 53.2%) did not report any metaphors. In all five countries, negative metaphors prevailed: 'Wasting time' (37/288), 'Useless' (32/288) and 'Handyman' (22/288) were the most negative reported metaphors on working a night shift. However, doing a night shift is also perceived as a 'Learning opportunity' (22/137), a 'New experience' (20/137) and an 'Opportunity to socialize with the profession' (14/137) as underlined by the positive metaphors. Conclusions: Students perceive night shift placements mainly as a negative experience, which has little to do with education. While planning night shift placements, nursing educators should responsibly consider the whole process of education, analysing not only the learning outcomes that should be achieved but also the position of students and their experience as a person. Clinical mentoring can be a key resource in supporting students in transforming their night shift placements' experiences into a more meaningful or worthwhile experience. Moreover, night shifts should be offered to more experienced students, independent in their self-learning processes and capable of managing the limited possibility of interacting with other team members and patients.